COMPARATIVE STUDY ON THE MANAGEMENT OF SUSTAINABLE TOURISTIC DEVELOPMENT IN BRASOV AND BRUSSELS COUNTIES - SANDU, Elena (Revista de turism - studii și cercetări în turism, 2014)
For decades, tourism has experienced steady growth and has strengthened its role in the economy, turning into a real industry that generates annual revenues exceeding 1.3 billion and created more than 260 million employments. With such performance, there is a pressing need to turn our attention to all the advantages and disadvantages that such development brings. Specifically, we must consider the impact of the tourism industry upon the socio-cultural, economic and environmental levels, in order to generate solutions that will ensure a healthy and responsible growth, ensuring the future of touristic destinations. To find a balance between the needs of tourists, host communities and the environment, reducing conflict and acknowledging mutual dependence, it takes a special approach in the management of destinations. This study aims to bring light to the need for sustainable development which appeared in today's society and continues the practice of a proper management of destinations, based on a comparison of documented scientific research methods between the two counties, Brussels and Brasov.